2017
DOI: 10.1186/s12906-017-1750-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-ethanolic leaf extract of Ziziphus abyssinica Hochst Ex A. Rich (Rhamnaceae) exhibits anti-nociceptive effects in murine models

Abstract: BackgroundDespite substantial advances in pain research and treatment, millions of people continue to suffer from pain and this has been attributed mainly to the unavailability of effective and safer analgesics. The use of plants as medicines is still widespread and plants constitute a large source of novel phytocompounds that might become leads for the discovery of newer, effective and safer alternatives. Various parts of Ziziphus abyssinica have been used in folk medicine in several African countries as pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Root extracts have been reported to possess anti-ulcerogenic ) and antidiarrheal properties. Our earlier research validated the analgesic effect of the hydro-ethanolic leaf extract of the plant in murine models (Boakye-Gyasi et al 2017). Qualitative phytochemical investigations have revealed that the aqueous and methanol fruit extracts of Z. abyssinica contain saponins, tannins, sterols and steroids, alkaloids, flavonoids and reducing compounds (Nyaberi et al 2010).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Root extracts have been reported to possess anti-ulcerogenic ) and antidiarrheal properties. Our earlier research validated the analgesic effect of the hydro-ethanolic leaf extract of the plant in murine models (Boakye-Gyasi et al 2017). Qualitative phytochemical investigations have revealed that the aqueous and methanol fruit extracts of Z. abyssinica contain saponins, tannins, sterols and steroids, alkaloids, flavonoids and reducing compounds (Nyaberi et al 2010).…”
Section: Introductionsupporting
confidence: 59%
“…Also the presence of carbohydrates, alkaloids, saponins, tannins, glycosides, anthraquinones and steroids were detected in Z. abyssinica aqueous root extract . Hydroethanolic leaf extract of the plant has been reported to contain tannins, phenols, alkaloids, triterpenes, flavonoids and phytosterols (Boakye-Gyasi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that DAE may have a direct effect on nociceptors associated with the early phase of the test. Additionally, the inhibition of pain in the second phase may be due to a modulatory effect on the release and/or synthesis of pro-inflammatory mediators [33] or subsequent cerebrospinal processing of pain after activation of the nociceptors.…”
Section: Discussionmentioning
confidence: 99%
“…dose-dependently inhibited acetic acid-, formalin-and glutamate-induced nociception with maximal inhibition of 86.29 ± 2.27%, 84.97 ± 5.35%, and 82.81 ± 5.97% respectively. The paw withdrawal latencies in both tail-immersion and carrageenan-induced hyperalgesia were also prolonged [109]. Moreover, the root extract reversed hyper-nociception induced by intra-plantar injection of TNF-α, IL-1β, bradykinin and prostaglandin E 2 via interactions with opioidergic, adenosinergic, ATP-sensitive potassium channels and nitric oxide cyclic GMP pathways [110].…”
Section: Ziziphus Abyssinica Hochst Ex a Rich (Rhamnaceae)mentioning
confidence: 95%